PENGARUH PERSEPSI SISWA TENTANG KARAKTERISTIK GURU MATEMATIKA TERHADAP PRESTASI BELAJAR MATEMATIKA - Emma Maria Sada Tawa; Yohanes Ovaritus Jagom; Agapitus Hendrikus Kaluge (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
This research aims to: (1) determine the perceptions of class VIII students regarding the characteristics of mathematics teachers at SMPN 2 Kupang; (2) determine the mathematics learning achievement of class VIII students at SMPN 2 Kupang; and (3) determine the influence of class VIII students' perceptions regarding the characteristics of mathematics teachers on mathematics learning achievement at SMPN 2 Kupang.. This research uses a simple regression analysis approach. The population in this study were class VIII students of SMPN 2 Kupang. The sample in this study was 30 students obtained through the cluster random sampling method. The data collection techniques used were questionnaires and tests. Data analysis was carried out descriptively and inferentially using SPSS 23. Descriptive research results showed that some students had a good perception of the characteristics of mathematics teachers with a good percentage 66.67% and had good mathematics learning achievement with a good percentage 83.3%. Inferentially shows there a significant influence between students' perceptions of the characteristics of mathematics teachers on mathematics learning achievement as indicated by the value of tcount (2,714) < ttable (1,701)   at the 5% significance level which means that H0 is rejected and there is a large influence of students' perceptions of the characteristics of mathematics teachers on achievement. studying mathematics is 20.8%.